(untitled) (Research, Society and Development, 2023)
Chronic pain is one that persists for more than three months and is one of the most frequent reasons for seeking health care, being considered a public health problem. Studies indicate that the number of people with chronic pain is increasing and an alternative treatment is the use of antidepressants. The aim of this study was to analyze the analgesic effect of antidepressants on chronic pain in patients treated at the rheumatology outpatient clinic of Sistema de Assistência à Saúde in Londrina-PR. The methodology used was the application of a questionnaire for data collection. After analyzing the 247 patients interviewed, it was observed that most patients with chronic pain were over 60 years old, female, married, and Catholic. Chronic pain was prevalent in patients with two or more comorbidities, with a predominance of systemic arterial hypertension. More than 80% of patients have felt pain for 1 year or more, and 67.9% reported feeling pain at the time of the interview. Pain was prevalent in the lower limbs and 76% of patients reported that pain had a negative impact on quality of life. There was a prevalence of osteoarthritis as a pain diagnosis. Among the interviewed patients, 88 use antidepressants and, among them, 82.2% have been using these drugs for 1 year or more and the most used ones are Duloxetine and Sertraline. Among those using antidepressants, 79.5% felt pain relief. Thus, it is concluded that the use of antidepressants helps to control chronic pain, being effective in its treatment.